The Complement Cascade as a Mediator of Human Malignant Hematopoietic Cell Trafficking - Lenkiewicz, Anna; Bujko, Kamila; Brzezniakiewicz-Janus, Katarzyna; Xu, Bing; Ratajczak, Mariusz Z. (Frontiers in Immunology, 2019)
The complement cascade (ComC) cleavage fragments C3a and C5a regulate the trafficking of normal, differentiated hematopoietic cells, although they do not chemoattract more primitive hematopoietic stem/progenitor cells (HSPCs). By contrast, human myeloid and lymphoid leukemia cell lines and clonogenic blasts from chronic myelogenous leukemia (CML) and acute myelogenous leukemia (AML) patients respond to C3 and C5 cleavage fragments by chemotaxis and increased adhesion. Consistent with this finding, C3a and C5a receptors are expressed by leukemic cells at the mRNA (RT-PCR) and protein (FACS) levels, and these cells respond to C3a and C5a stimulation by phosphorylation of p44/42 MAPK and AKT. However, neither of these ComC cleavage fragments have an effect on cell proliferation or survival. In parallel, we found that inducible heme oxygenase 1 (HO-1) - an anti-inflammatory enzyme, is a negative regulator of ComC-mediated trafficking of malignant cells and that stimulation of these cells by C3 or C5 cleavage fragments downregulates HO-1 expression in a p38 MAPK-dependent manner, rendering cells exposed to C3a or C5a more mobile. We propose that, while the ComC is not directly involved in the proliferation of malignant hematopoietic cells, its activation in leukemia/lymphoma patients (e.g., as a result of accompanying infections or sterile inflammation after radio-chemotherapy) enhances the motility of malignant cells and contributes to their dissemination in a p38 MAPK–HO-1 axis-dependent manner. Based on this idea, we propose that inhibition of p38 MAPK or upregulation of HO-1 by available small-molecule modulators would have a beneficial effect on ameliorating expansion and dissemination of leukemia/lymphoma cells in clinical situations in which the ComC becomes activated. Finally, since we detected expression of C3 and C5 mRNA in human leukemic cell lines, further study of the potential role of the complosome in regulating the behavior of these cells is needed.